FOOD DELIVERY SERVICE APPLICATION DURING PANDEMIC COVID-19 (Journal of Technology and Operations Management, 2022)
Online food deliveries are third-party tools that facilitate for online purchase and delivery, present an alternate way of ordering that looks to be gaining traction. This study will examine consumer acceptance behaviour towards food delivery application (FDA) during pandemic COVID-19 and the factor that lead them to accept or reject of using FDA. This study also will identify food delivery service applications that usually consumer use. This study will focus on Northern Malaysia, Kulim area which is covering the rural and urban areas. In order to achieve this study, the researcher has used a qualitative method which is data collected through semi-structured interviews. The result shows that there are four factors that contribute to the acceptance and rejection of online food delivery applications which is time, quality, safety, and price. Furthermore, there are four respondents that accept and one respondent rejects using FDA. The most favorite application that consumers use is Food Panda. The FDA helps many consumers during this pandemic season. Therefore, a variety of applications and service improvements are needed to provide customer satisfaction.